HISTORY AND ORIGIN OF TURKISTAN MEDICINE - Ochilova Oydinoy (Western European Studies, 2025)
This article presents information about the state of Turkestan medicine, the doctors who worked at that time and their treatment methods in English-language sources.
Keywords: Turkestan medicine; Western tourists